Germination of rubber (Hevea Brasiliensis) seeds using different types of problematic soils as a medium / Fatin Nurfarhana Mohd Shahril - Mohd Shahril, Fatin Nurfarhana (Faculty of Plantation and Agrotechnology, 2019)
Large distribution of problematic soils in Malaysia such as peat soil, acid sulphate soil and sandy soil much potential of planting medium in agriculture sector through a proper management. Therefore, this aim of the study were to determine the soil chemical properties and to evaluate the growth of rubber seedlings grown in peat soil, acid sulphate soil and sandy soil, respectively. In this study, the clay loam soil of class 1 which is common in rubber nursery was used as control to compare the growth performance of rubber seedlings. Results showed that acid sulphate soil release higher concentration of P, K and Mg with positive growth of rubber seedlings throughout the experimental weeks as compared to other soil types. It is suggested that a thorough study need to be done to optimize the potential of acid sulphate soils as germination medium of rubber seedlings in future.